The Influence of Social Media on Students’ Reading Ability - Dwi Rulli Rahmawati; Semi Sukarni; Sri Widodo (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2020)
The objectives of the research is to find out whether is any positive and significant influenceof influence of the use social media on students’ reading ability at the eighth grade of SMP Negeri 4Purworejo in the academic year of 2019/2020.. The sample involved 50 students by applying purposivesampling. The population of this study is the eighth grade students of SMP Negeri 4 Purworejo in theacademic year of 2019/2020. The total of the eighth grade students is 256 students. formula.Theinstruments to take the data by questionnaire to observing the use of social media and by reading test toobserving the reading comprehension skill. Mean and standard deviation are used in the descriptiveanalysis, while test of linearity and hypothesis is used in the inferential analysis. The main result of thisresearch is (1) the use of social media can be categorized in sufficient level with M = 74.56, the SD =9.73 and S = 94,741 at the range 70-79. (2) the students’ reading ability can be categorized in excellentlevel with M = 77.8, the SD = 16.394and S = 268.776 at the range 80 – 100. (3) the result of hyphotesistest shows that the value of correlation is 0.312 which is higher than 0.279 rtable 5%. It means that theuse of social media influence the students’ reading ability as big as 9.8% and the residue is 90.2%influenced by other factor. The significant value of regression based on SPSS 16.0 is 0.027which islower than 0.05. It means that there is a positive and significant influence between two variables.